High porosity materials as volumetric receivers for solar energetics - Fend, Thomas (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
This paper gives a brief overview on the research activities of the Solar Technology Department of the German Aerospace Center on porous materials for solar tower technology. Firstly, a brief introduction to solar tower technology is given. Then, the function of the central component of tower technology, the volumetric air receiver, is described in detail and examples as well as experimental results of receiver tests are given. Results of numerical studies are presented, which have been carried out to characterize air flow stability in receiver systems. Approaches presently used to model the interior temperatures of the receiver are described. Next spin-off applications such as particle filters or cooling systems are presented, which are dominated by similar physical phenomena and which can be treated with the same experimental and numerical methods. Finally, information is given about the Jülich Solar Tower, which is the first test power station that makes use of the solar air receiver technology.
Optica Applicata, Vol. 40, 2010, nr 2, s. 271-284
Keywords: optyka; solar tower technology; porous materials; volumetric air receiver; concentrating solar power